2020
DOI: 10.4244/eij-d-19-00428
|View full text |Cite
|
Sign up to set email alerts
|

Observational multicentre registry of patients treated with IMPella mechanical circulatory support device in ITaly: the IMP-IT registry

Abstract: Aims:The aim of this study was to investigate nationwide trends and clinical outcomes of the Impella device for cardiogenic shock (CS) and high-risk percutaneous coronary intervention (HR-PCI). Methods and results:The IMP-IT study was a multicentre observational national registry which enrolled all patients treated with Impella 2.5, Impella CP, Impella 5.0 and Impella RP, both for CS and HR-PCI indications, across 17 Italian centres from 2004 to June 2018. A total of 406 patients were included: 229 had CS (56.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 16 publications
6
64
1
Order By: Relevance
“…In a recent multicentre study from Italy, AMICS was the indication for Impella in 75.1% of cases. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent multicentre study from Italy, AMICS was the indication for Impella in 75.1% of cases. 22 …”
Section: Discussionmentioning
confidence: 99%
“…More extensive revascularization was associated with improved 90-day MAE compared Also, the comparison of mortality and adverse event rates across these studies is challenging given the variable baseline patient characteristics and the threshold for device usage. Nonetheless, the allcause mortality at 1-year among patients supported with Impella during HR-PCI were similar at 15.6% in the IMP-IT registry58 and 15.3% in the analysis by Azzalini et al21 Burzotta et al investigated the effect of extent of revascularization on LVEF and survival in 86 patients undergoing Impella-supported PCI in the Roma-Verona registry 59. At a mean follow-up of 14 months, the all-cause mortality rate was 10%.…”
mentioning
confidence: 86%
“…45,46 PROTECT III is an ongoing, prospective, FDA post-approval study of Impella-supported HR-PCI patients. Between 2017 and 2019, a total of 898 Superior hemodynamic support during HR-PCI 45 Supports longer rotational atherectomy procedures during HR-PCI 48 Improved clinical outcomes up to 90 days after HR-PCI 45,[49][50][51] Extensive revascularization with Impella associated with improved outcomes 53 Protects against in-hospital acute kidney injury 55,56 Improved survival and ejection fraction in the long term 21,[57][58][59] Beneficial in patients with LVEF >35% undergoing HR-PCI 61 In Protect II, Impella provided superior hemodynamic support compared to IABP (maximal decrease in cardiac power of 0.04 ± 0.24 W with Impella versus 0.14 ± 0.27 W with IABP; p=0.001). 45 Only 6% of Impella patients were discharged from the catheterization lab on the device, compared to 37% of IABP patients.…”
Section: Impellamentioning
confidence: 99%
“…Bleeding complications over time demonstrated that the variability in bleeding risk seen across centres has not changed meaningfully over the last 15 years (Figure 1). 7,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Given the broad scope of bleeding complications (comprising both access and non-access-related bleeding during PCI), often complicated by pre-existing anaemia and the inclusion of some urgent HR-PCI patient populations, this variability is not surprising. Likewise, many series reported relatively low numbers of cases over extended time periods, suggesting that any advantages of increased operator skill, using best practices accrued through increasing experience, could not be ascertained.…”
Section: Trends In Bleeding and Vascular Complications Over Timementioning
confidence: 99%